Implementasi Aplikasi Digital My Darling (Masyarakat Sadar Lingkungan) dalam Memingkatkan Kesadaran Kebersihan dan Keamanan Lingkungan di Kelurahan Kadu Agung - Saryani, Saryani; Asmarani, Nindya Putri; Permatasari, Febi Anjelina; Raihandi, Muhammad Baihaqi; Baihaqi, Zidane (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The utilization of digital technology in community service activities has become one of the effective strategies to address environmental problems at the local level. This community service activity aims to implement the My Darling (Masyarakat Sadar Lingkungan) digital application as a waste bank management tool to enhance public awareness of environmental cleanliness and safety in Kadu Agung Village, Tigaraksa District, Tangerang Regency. The implementation methods include initial observation, socialization, application implementation, assistance, and evaluation. The results show that the use of the My Darling application facilitates waste bank management, increases community participation in waste management, and encourages the creation of a cleaner and more orderly environment. The main challenges encountered are related to the community’s digital literacy; however, these can be minimized through continuous assistance. This activity is expected to serve as a model of digital technology–based community service that can be replicated in other regions.